2008
DOI: 10.1016/j.bbmt.2008.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Cytomegalovirus pp65 and IE-1 Specific Cytotoxic T Lymphocytes for Cytomegalovirus-Specific Immunotherapy Following Allogeneic Stem Cell Transplantation

Abstract: Adoptive immunotherapy with antigen specific cytotoxic T lymphocytes (CTL) has been shown to be effective in restoring cellular immunity to cytomegalovirus (CMV) and preventing viral reactivation following allogeneic stem cell transplantation (SCT). In order to develop a cost-effective, relatively rapid method of CMV CTL expansion, we investigated the use of a pool of overlapping CMV peptides. Since the possibility exists of vaccinating CMV sero-negative donors, and these individuals may have T cell responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…CMV pp65 or IE1 specific cytotoxicity and IFN-γ production was present in each of these donors, and data from donor CTL that were infused are presented in Figure 1. This is consistent with our previous findings in which CMV pp65 or IE1 specific CTL could be cultured from the majority of healthy donors 17 . The average pp65 specific cytotoxicity for the products was 37 % (range 21-58 %) and 30% for IE1 (range 21%-38%).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…CMV pp65 or IE1 specific cytotoxicity and IFN-γ production was present in each of these donors, and data from donor CTL that were infused are presented in Figure 1. This is consistent with our previous findings in which CMV pp65 or IE1 specific CTL could be cultured from the majority of healthy donors 17 . The average pp65 specific cytotoxicity for the products was 37 % (range 21-58 %) and 30% for IE1 (range 21%-38%).…”
Section: Resultssupporting
confidence: 93%
“…Multiple-color staining of immunophenotypic markers, both surface and intracellular, was performed as previously described 17 . In brief, T cells were incubated with equal numbers of stimulators, including autologous BB pulsed with pp65 and IE1 overlapping peptides or B blasts infected with either vaccinia encoding pp65 or IE1, and autologous and allogeneic BB, in RPMI 1640 with 10% FCS and in the presence of 10 μg/ml brefeldin A (Sigma) at 37°C for 5 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, attention should be focused on adoptive cellular immunotherapy, such as donor-derived NK subsets [38], as well as CMV specific cytotoxic T lymphocytes [39]. These approaches can potentially improve early immune recovery and decrease the incidence of CMV antigenemia following unmanipulated haploidentical transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that such T cells are safe, efficacious, and cost-effective. [15][16][17] Here, we show that this approach can also be extended to cord blood.…”
Section: Discussionmentioning
confidence: 76%